2013
DOI: 10.1128/aac.00510-13
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Treatment Failure of Polymyxin B Monotherapy for Carbapenem-Resistant Klebsiella pneumoniae Infections

Abstract: I nfections caused by carbapenem-resistant Klebsiella pneumoniae (CRKP) have been associated with poor outcomes. An overall mortality rate of 48% is reported for patients with CRKP, compared to 26% for those with carbapenem-susceptible K. pneumoniae infections (1). CRKP isolates confer resistance through the production of K. pneumoniae carbapenemases (KPCs), which are able to hydrolyze all currently available ␤-lactams, including carbapenems (2). Due to additional mechanisms of resistance commonly found in KPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 24 publications
0
44
0
2
Order By: Relevance
“…A study of 40 patients receiving monotherapy with polymyxin B for KPC-Kp infection identified renal failure as the only risk factor for treatment failure. Renal failure, in isolation, has also been reported to be a mortality risk factor in other studies of cancer patients with bacterial infections, as well as in studies of KPC-Kp infections in other populations [30,[43][44][45].…”
Section: Discussionmentioning
confidence: 94%
“…A study of 40 patients receiving monotherapy with polymyxin B for KPC-Kp infection identified renal failure as the only risk factor for treatment failure. Renal failure, in isolation, has also been reported to be a mortality risk factor in other studies of cancer patients with bacterial infections, as well as in studies of KPC-Kp infections in other populations [30,[43][44][45].…”
Section: Discussionmentioning
confidence: 94%
“…2,1518,29,30 Furthermore, suboptimal dosing may promote the emergence of polymyxin resistance. 2932 In the present study, we first examined the in vitro apoptotic effect of the major lipopeptide components of polymyxin B and colistin on human kidney proximal tubular cells (HK-2). 33 The HK-2 cells were chosen in this study, as pharmacokinetic studies have demonstrated that polymyxin B and colistin are significantly reabsorbed by renal tubular cells after filtration by glomeruli.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, combination therapy was an independent predictor of survival and patients with advanced age were more likely to have received monotherapy. In contrast, another retrospective study that examined polymyxin B monotherapy for CR-KP infections found a treatment success rate of 73%, including 82% for bacteremia [10]. However, it is concerning that 3 out of 40 patients treated with polymyxin B developed breakthrough infections from polymyxin-resistant organisms while on therapy.…”
mentioning
confidence: 87%
“…However, it is concerning that 3 out of 40 patients treated with polymyxin B developed breakthrough infections from polymyxin-resistant organisms while on therapy. Because these studies [7][8][9][10] were retrospective, the results may have been influenced by confounding factors like comorbidities, severity of sepsis and timing of the initiation of antibiotics. In a recent report, Demiraslan et al [11] compared colistin or tigecycline monotherapy to colistin plus tigecycline in a murine model of CR-KP sepsis.…”
mentioning
confidence: 99%